Una revisión de la literatura sobre la relación causal entre los factores oclusales (FO) y los desórdenes temporomandibulares (DTM). VI: conclusiones finales - Rodolfo Acosta-O; Blanca Patricia Rojas-S (Universidad de Antioquia, 2009)
Temporomandibular disorders (TMD) are a group of musculoskeletal/rheumatologic disorders of the orofacial region that involves directly the masticatory system. The etiology of TMD is controversial and even though different factors such as anatomical, psychological, traumatic, pathophysiologic have been considered as contributors in the development of DTM, the current evidence does not allow establishing a clear relationship with any factor. However, the occlusal factors (OF) through history have traditionally been associated with the etiology of TMD and many studies have been done to clarify the relationship between DTM and OF. With regard to the importance of the occlusion in the etiology of TMD, there is currently a discrepancy not only between general dentists and TMD Specialists but also among clinicians of this last group. This diversity of opinions indicate the need for continuous analysis of the possible relation between OF and TMD. This first article presents a review of the epidemiologic descriptive studies found in the literature that have been carried out to study the relationship between DTM and OF. The analysis of these epidemiologic reports indicate that there is not a tendency to favor any of the OF to be related with the etiology of TMD and that possibly other factors should be considered in the development of TMD.